VERNAKULARISASI DALAM TAFSIR BASA SUNDA: Studi Atas Tafsir Nurul Bajan Karya Muhammad Romli Dan H.N.S Midjaja - Nurmawati, Reni; Mualim, Mohamad; Shofa, Ida Kurnia (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2023)
This article examines one of the most famous Sundanese tafsir books of its time and was written by a modernist Islamic figure in West Java, namely Muhammad Romli and H.N.S Midjaja. The book of tafsir is entitled Tafsir Qur'an Basa Sundanese Nurul Bajan. This tafsir was not completed in 30 juz, only reaching the third juz of Surah Al-Imran verse 91. This tafsir was written using Sundanese Latin language and script with old spelling that had not been perfected. There are three cultural aspects that influence the process of interpreting the Koran into Sundanese, including language stratification, traditional Sundanese expressions, and Sundanese nature. This research aims to examine the elements of vernacularization in Nurul Bajan's interpretation, which includes Sundanese language etiquette (Sundanese language steps), traditional Sundanese expressions, and Sundanese natural descriptions. This type of research is library research and is classified as qualitative research. This research uses a descriptive-analytical method using the vernacularization theory approach initiated by Anthony H. Johns. The results of this research can be concluded that Tafsir Nurul Bajan contains forms of vernacularization consisting of language manners (undak-usuk basa) which include the words arandjeun, manehna, ngadeg, abdi, wife, bodjo, garwana, pameget, uninga, ngadamel, and wallon. Traditional expressions include the words Mung kedah buleud determination and Ngahidji sabilulungan. A description of the nature of Sundanese which includes the words